The Italian approach to rare diseases and the action of the Italian National Centre for Rare Diseases (Italian Journal of Public Health, 2009)
The European Commission, recognizing that a number of healthcare and knowledge issues are common to allrare diseases in spite of the wide variety of their clinical manifestation, has recently initiated the promotionof national plans and comprehensive strategies for improving the provision of care to rare disease patients.In Italy, for some time, a number of coordinated initiatives have been undertaken at National and Regionallevel in order to provide quality care to rare disease patients. Some of these initiatives anticipate therecommendations at the European Union level.A key legal instrument has been the Ministerial Decree 279/2001 which established, with the collaboration ofthe Regions, the national network for the surveillance, diagnosis, treatment and cost exemption for rarediseases. Other regulations facilitate access to drugs and to assistance for the disabilities associated withrare diseases. More recently specific initiatives have been adopted to foster research on rare diseases and theinvolvement of patients in decision making regarding rare diseases.Another key step in the development of an effective strategy to tackle rare diseases in Italy, has been theestablishment of the National Centre for Rare Diseases. The Centre is currently developing a wide variety ofinitiatives: some contribute to the full implementation of the national legislative provisions and to thecoordination of activities among the Regions; others aim to develop autonomous initiatives within its missionof research, provision of technical expertise and documentation as well as information on rare diseases.
Keywords: rare disease; surveillance; genetic test; quality assurance; coding; social inclusion; patients’ empowerment